Faith as a correlate of social work treatment success among women with infertility in public hospitals in Ibadan (2024)
In recent times, there has been an increase acceptance of treatment of infertility’s comprehensive nature. The study examined how faith correlates with the success of social work interventions among infertile women in public hospitals in Ibadan. Utilizing a mixed-method approach. Data was gathered from 150 participants through structured surveys and interviews. Analysis of the data showed a significant association between faith and social work interventions (r2~0.62l; n=IOO; P<01), highlighting the pivotal rote of faith in improving treatment outcomes. Furthermore, the study identified that faith has a substantial impact on social work intervention treatment outcomes (F (99) =3.697; P<01. Recommendations stemming from the study encompass integrating faith into social work practices, raising awareness among social work professionals regarding the efficacy of faith-based approaches, and advocating for further research into the impact of faith on treatment outcomes.